Reservoir Temperature Calculation and Modeling for Convective Geothermal Systems: Case Study of Five Major Hot Springs in Lushan, Henan, China - Wang Qi; Zhou Dongxu; Liao Jiajia; Liu Yuntao; Wang Xinyi (Geofluids)
The thermal storage temperature and water-rock interaction process of the Lushan convective geothermal system (Qinling stratigraphic zonation fracture zone in China) are clarified by using surface cold water and geothermal fluid as the research objects. In this study, a conceptual model of the temperature profile of the geothermal system in the study area was developed using surface temperature inversion, the cation temperature scale, the SiO2 temperature scale method, the mineral equilibrium phase method, the silicon-enthalpy model, the FixAl method, and the Cl-enthalpy model. The inversion temperature at the surface is in the range of 33-39°C, and the temperature difference indicates the direction of the Checun-Lushan fracture. The study area is recharged from atmospheric precipitation, and the temperature of the recharge area is approximately 5.8–7.7°C (the temperature of the alkali field is approximately 10°C), and the recharge elevation is approximately 1200 m. The thermal storage pattern in the study area is near-surface hydrothermal thermal storage transferred to shallow thermal storage and then to deep thermal storage. The near-surface hydrothermal thermal storage temperature is at a constant temperature of 60°C, and the shallow thermal storage temperature is calculated by K-Mg and Li-Mg geothermometers to be between 99 and 112°C. The thermal storage temperature is simulated using the FixAl method, with deviation values ranging from 2.9% to 15.0%. The silicon-enthalpy model calculates the deep thermal storage temperature to be between 181 and 230°C. The mixing ratio of geothermal water in the study area is extremely high, with a cold water mixing ratio of 85.4–94.8%. The home ground fluid temperature was estimated to be approximately 282°C using the Cl-enthalpy model. The main thermally controlled conductivity channel in the study area is the Checun-Lushan fracture zone. The water vapor formed by convection at depth moves upward to approximately 5 km to form a deep thermal reservoir, and this convection and upward movement cause it to mix with cold water from the fracture zone to form a shallow thermal reservoir, which moves to the near-surface, forming a hydrothermal-type reservoir, which is later discharged in the form of a spring. The conceptual model of geothermal system temperature established in this study provides a basis for further development and utilization of Lushan hot springs and provides guidance for future thermal storage temperature calculations of convection-type geothermal systems in uplifted mountains.